Alaṅkārikā - Śāha, Nirmaḷā Campakalāla (Ena. Ema. Tripāṭhī Limiṭeḍa, 1949)
Designs for floor and wall decoration (Kolam) used in Gujarat, India; includes explanation on the making of Kolam and its significance.